Understanding cognitive and psychosocial correlates of spoken discourse skills in adolescents with and without acquired brain injury. - Hill, Elizabeth Jane (Curtin University, 2020)
Many adolescents with a brain injury have difficulties with everyday communication, or discourse, and therefore intervention at the discourse level is crucial. However, tools to assess adolescent discourse are scarce. Lizz’s PhD consisted of the development of a much needed discourse assessment tool, which enabled an exploration of the relationship between language, cognition and psychosocial health in teenagers without brain injury, and how they may relate to communication difficulties following brain injury